2021
DOI: 10.1111/jonm.13304
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Study of Nurse Managers’ and Assistant Nurse Managers’ Experiences during the COVID‐19 Pandemic in the United States

Abstract: Aim To understand the experiences of hospital nurse managers and assistant nurse managers during the COVID‐19 pandemic in the United States. Background Little research has been published about the experiences of nurse managers during the COVID‐19 pandemic. Experiences of front‐line nurses have been well documented. This is the first phenomenological study to date in the United States on experiences of hospital nurse managers during the COVID‐19 pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
112
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(147 citation statements)
references
References 26 publications
(38 reference statements)
7
112
2
5
Order By: Relevance
“…Nurse managers may bear the burden of supporting frontline nurses yet may not have the unit and organizational resources needed during times of crisis. 17 A potential limitation of this study is response bias. Respondents may have been experiencing more or less stress than those who did not respond.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Nurse managers may bear the burden of supporting frontline nurses yet may not have the unit and organizational resources needed during times of crisis. 17 A potential limitation of this study is response bias. Respondents may have been experiencing more or less stress than those who did not respond.…”
Section: Discussionmentioning
confidence: 91%
“…The COVID-19 pandemic will most likely have a tremendous influence on ICU nurses' mental health and potentially their continuation in the workforce. Although the experiences of nurses in other countries, [12][13][14][15][16] nurse managers, 17 nurses from 1 ICU, 18 and HCWs in general [19][20][21] have been reported, at the initiation of this survey, we found no published studies that described the national ICU nurse experience in the United States. To fully support ICU nurses currently and after the pandemic, it is of critical importance that we explore nurses' perspectives about working in ICUs during this time.…”
mentioning
confidence: 79%
“…Other studies on COVID‐19 have similarly reported challenges such as shortage of workforce, heavy workloads and shortage of personal protective equipment as the problems of nurses during this pandemic (Havaei et al, 2021 ; Mo et al, 2020 ; Shahrour & Dardas, 2020 ). However, in one study in the United States, nurse managers did not mention a shortage of, or problems with, facilities and personal protective equipment (White, 2021 ). In the recent decade, the shortage of nurses in Iran has been a challenge for health care managers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relevant role of nurse managers during the pandemic, little is known about their experiences (White, 2021 ). This qualitative study contributes to the knowledge on the unique experiences of frontline nurse managers during the pandemic, which can help plan and prepare nurse managers for future health disasters, including subsequent waves of COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…Published editorials have provided recommendations for effective leadership during the pandemic and suggest the requirement for courageous leaders with sound knowledge (Rosser et al, 2020 ; Shingler‐Nace, 2020 ). Only one study published on nurse managers' experiences during the pandemic with a qualitative approach has been identified to date, although the study did not focus only on frontline nurse managers and was carried out in another context (White, 2021 ). According to this phenomenological study, the new role of nurse managers during the pandemic focuses on the emotional well‐being of their staff and continual communication (White, 2021 ).…”
Section: Introductionmentioning
confidence: 99%